Экономика России: учебное пособие / В. В. Виноградов - Виноградов Василий Васильевич (Homo faber, 2001)
Экземпляры: аб. (2002) / Инвентарный номер: 44156 / Цена: / Сис.шифр: 65.9(2) / Авт.знак: В 49 / ГРНТИ: 06 / ББК: 65.9(2) я73